1984
DOI: 10.1071/ar9840279
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of particulate markers for the estimation of digesta flow from the abomasum of sheep offered chopped oaten hay

Abstract: Five sheep with simple cannulae in the rumen and abomasum were given a diet of chopped oaten hay at 95-98% of ad libitum intake from continuously moving belts. Flows of digesta from the abomasum were estimated by a double marker method by reference to 51Cr-EDTA as the fluid marker, and either 103Ru-P, lignin, or acid insoluble ash (AIA) as the particulate marker. Estimates were also made by reference to lignin as a single marker. Estimates of the weight of digesta leaving the abomasum daily were unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…Lindberg (1988) indicated that ruminal outflow of small particles is related to ruminal outflow of water. Egan and Doyle (1984) demonstrated with sheep that very small particles flowed at a rate close to that of the fluids, and that the PPR from the reticulorumen increased as particle size decreased. Because of entrapment in the reticuloruminal raft, even the finest particles flowed from the reticulorumen more slowly than the fluid fraction; a small proportion, however, seemed to flow with the fluid fraction (Faichney, 1986).…”
Section: Resultsmentioning
confidence: 96%
“…Lindberg (1988) indicated that ruminal outflow of small particles is related to ruminal outflow of water. Egan and Doyle (1984) demonstrated with sheep that very small particles flowed at a rate close to that of the fluids, and that the PPR from the reticulorumen increased as particle size decreased. Because of entrapment in the reticuloruminal raft, even the finest particles flowed from the reticulorumen more slowly than the fluid fraction; a small proportion, however, seemed to flow with the fluid fraction (Faichney, 1986).…”
Section: Resultsmentioning
confidence: 96%
“…This could explain the shorter TMRT observed for even-chain alkanes adsorbed into cellulose powder (C 24 and C 28 alkanes) in comparison with the other matrices. Nevertheless, even the very small particles have a longer retention time than fluid, probably owing to sieving effects of the reticuloruminal mass, 24 explaining the slightly longer TT and TMRT for both C 24 and C 28 alkanes in comparison with those for Co-EDTA, a liquid phase marker. The different retention times (TMRT ) among markers have to be mainly attributed to the different TT values estimated, because no differences were observed in the values of k 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Co-EDTA, prepared following the procedure of Udén et al, 17 was dissolved in distilled water (7.5 g of Co-EDTA in 200 ml of water), and 30 ml of the solution was administered to each animal. Total amounts of faeces voided during each time interval were collected in buckets at 6,9,12,16,20,24,28,32,38,44,53,65,77,89,114,137 and 161 h post-dosing. At each sampling time the bulk faecal output of each animal was weighed, mixed thoroughly and sampled.…”
Section: Markermentioning
confidence: 99%
“…The double-marker method requires that the markers used be distributed evenly throughout their respective phases (Faichney, 1975 a). However, lo3Ru-P is not evenly distributed throughout the particulate matter (Faichney,(1 982) so that reconstitution factors depending on this marker may not adequately correct for relatively large sampling errors (Faichney, 1982;Egan & Doyle, 1984). Accordingly, where reconstitution factors for abomasal digesta were greater than 0.2-0.3, the faecal output of ADL was compared with its abomasal flow assuming there was no post-rumen disappearance of ADL (Fahey & Jung, 1983).…”
Section: R E S U L T Smentioning
confidence: 99%